The relationship between confidence and self-concept - Towards a model of response confidence. - Kröner, Stephan; Biermann, Antje (Intelligence, 2007)
According to Stankov [Stankov, L. (2000). Complexity, metacognition and fluid intelligence. Intelligence, 28, 121–143.] response confidence in cognitive tests reflects a trait on the boundary of personality and abilities. However, several studies failed in relating confidence scores to other known traits, including self-concept. A model of response confidence is proposed which predicts that confidence judgements do reflect self-concept, but only to the extent that they do not reflect a calibration process based on task-inherent cues. In the current study, 101 students completed various tests of cognitive abilities and skills as well as scales of the SDQ III measuring general academic and problem-solving self-concept. As expected, self-concept predicts a significant proportion of variance in the confidence factor that is over and above the influence of test scores.<br